KITE GAMES SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN KOORDINASI SENSOMOTORIK PADA ANAK AUTIS - Swastika, Risma Arindha; Pawestri, Retno Dwi; Martadi, Husein (Pelita - Jurnal Penelitian Mahasiswa UNY, 2015)
This research is aimed at revealing the effectiveness of "Kite Games" in improving the sensomotoric coordination ability of the autistic children. The type of the research is quasi experiment by employing the quantitative approach. The pre test, treatment, and post test were implemented to improve the ability of the sensomotoric coordination of the autistic children. The research variables were the use of Kite Games as the free variable and the sensomotoric coordination ability as the bound variable. The research subjects were autistic elementary school children meeting certain criteria. The data were collected through observations, interviews, and tests. With the success criteria of 80%, two children met the criteria. So, the kites were effective to improve the sensoric coordination ability. It shows that the kites as media could be developed into a more innovative media. The improvement o f the social interaction ability of the children was shown in their willingness to initiate a communication with others. Key words: kites, autism, sensoric coordination